The psychology of branding : Developing and testing visual identities for a self-portrait studio - Kosheleva, Polina; Zichová, Tereza; Dědic, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
In today's visually saturated market, a brand’s success may depend on how effectively its visual identity captures attention and builds trust. This bachelor thesis explores whether a visual identity developed using psychological principles — such as color psychology, emotionally resonant typography, and logo design followed by Gestalt principles — leads to improved brand perception and engagement. The main objective of this thesis is to quantitatively assess the impact of psychology-based visual identity on brand recall, emotional response, and social media interaction. Based on the research findings, a practical framework was made, offering guidelines for businesses on how to apply psychological principles if they want to create or change a visual identity. The research was guided by five questions focused on memorability, logo perception, emotional response to main visual identity components, engagement in Instagram ads, and emotional connection. Two different visual identities were created for a modern self-portrait studio called Narcis Studio — the first one was made with the implementation of psychological theory, and the second one did not follow these principles. Their performance was evaluated through a 15-day A/B testing campaign on Instagram, with an equal ad budget of 1,725 CZK for each version, and a structured questionnaire completed by 93 respondents aged 18–34. The psychology-based identity consistently outperformed the alternative: it was perceived as more trustworthy, memorable, and emotionally engaging, and it had significantly higher engagement on Instagram. These findings confirm the importance of psychology-informed branding and form the basis of a practical guide for companies that want to have emotionally effective visual identities.
Vedoucí práce: Tereza Zichová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses